2016
DOI: 10.1016/j.cell.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Redefining the Translational Status of 80S Monosomes

Abstract: Fully assembled ribosomes exist in two populations: polysomes and monosomes. While the former has been studied extensively, to what extent translation occurs on monosomes and its importance for overall translational output remain controversial. Here, we used ribosome profiling to examine the translational status of 80S monosomes in Saccharomyces cerevisiae. We found that the vast majority of 80S monosomes are elongating, not initiating. Further, most mRNAs exhibit some degree of monosome occupancy, with monoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
181
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(209 citation statements)
references
References 54 publications
16
181
1
Order By: Relevance
“…1C). A recent study by Heyer and Moore has shown that a certain subset of mRNAs in Saccharomyces cerevisiae can be translated by monosomes (Heyer and Moore 2016). However, the study did not show that UPP genes are translated by monosomes.…”
Section: Differential Mrna Translation During Amino Acid Starvationcontrasting
confidence: 50%
“…1C). A recent study by Heyer and Moore has shown that a certain subset of mRNAs in Saccharomyces cerevisiae can be translated by monosomes (Heyer and Moore 2016). However, the study did not show that UPP genes are translated by monosomes.…”
Section: Differential Mrna Translation During Amino Acid Starvationcontrasting
confidence: 50%
“…Translation or ribosome binding of lncRNAs, which contain small ORFs (sORFs) and thus possibly produce micropeptides (Slavoff et al 2013;Ruiz-Orera et al 2014;Raj et al 2016) has been reported in multiple species, including yeast (Ingolia et al 2014;Smith et al 2014), fruit flies (Dunn et al 2013;Aspden et al 2014), zebrafish (Chew et al 2013;Bazzini et al 2014), and mammals (Chew et al 2013;Zhou et al 2013;Ingolia et al 2014;van Heesch et al 2014;Fields et al 2015;Ji et al 2015;Calviello et al 2016; for review, see Ingolia 2016). Moreover, a recent study provided evidence that a vast majority of monosomes is actively elongating and translating sORFs (Heyer and Moore 2016). Thus, ribosome binding/translation of some lncRNAs occurs and appears compatible with efficient cellular protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…(4) Discard the supernatant and re-suspend the pellets in 10 ml ice-cold polysome profile buffer (PPB) (10 mM Tris-HCl pH 7.5, 50 mM NH 4 Cl, 10 mM MgCl 2 , 1 mM DTT, 100 µg/ml chloramphenicol) [11].…”
Section: S Aureus Cell Extract Preparationmentioning
confidence: 99%
“…Due to its aggressiveness and to the existence and proliferation of many multidrug-resistant strains, S. aureus is a major public health concern [13]. To our knowledge, only S. aureus ribosomes and not the polysomes have been studied [4,[14][15][16][17][18].…”
mentioning
confidence: 99%
See 1 more Smart Citation